2021
DOI: 10.3390/molecules26237295
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Absorption Effects on the Mechanical Properties of Sandwich Biocomposites with Cork Core and Flax/PLA Face Sheets

Abstract: The aim of this study was to evaluate the moisture absorption behaviour and its influence on the mechanical properties of newly developed sandwich biocomposites with flax fibre-reinforced poly-lactic acid (PLA) face sheets and soft cork as the core material. Three different types of sandwich biocomposite laminates comprised of different layup configurations, namely, non-woven flax/PLA (Sample A), non-woven flax/PLA and cork as core (Sample B) and non-woven flax/paper backing/PLA, cork as core (Sample C), were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In contrast, the strain at failure of the specimens increased after they were water aged. Te reduction in tensile strength and modulus of specimens after water ageing is attributed to the debonding efect of water molecules [39]. Natural fbers are more hygroscopic and absorb more water.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…In contrast, the strain at failure of the specimens increased after they were water aged. Te reduction in tensile strength and modulus of specimens after water ageing is attributed to the debonding efect of water molecules [39]. Natural fbers are more hygroscopic and absorb more water.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…In the step 2, The PLA film and flax/PLA were compressed at 190 • C for 5 min, under a pressure of 1 bar, and in step 3, the compressed laminates were consolidated. The detail steps of the fabrication process are provided in the authors' previous article [40].…”
Section: Fabrication Of Composite Laminatesmentioning
confidence: 99%
“…All of these studies have reported significant loses of mechanical properties with increase in moisture uptake as compared to the dry specimens. The reduction of the mechanical performance is mainly attributed to the swelling of natural fibres, delamination at the fibre-matrix interface and widening of the gap between the fibre bundles, under the effect of water absorption, which in turn affect the overall performance and the durability of composites [40].…”
Section: Introductionmentioning
confidence: 99%